SCIENTIFIC PAPER WRITING TRAINING FOR STUDENTS OF CLASS XII OF SMA 1 PERTIWI PADANG - Yulianti, Upit; Fitri, Rahayu; Helda, Trisna (RANGKIANG: Jurnal Pengabdian Pada Masyarakat, 2025)
This community service activity is in the form of scientific writing training for grade XII students of SMA Pertiwi 1 Padang. The low scientific writing skills of the students can be seen from the writing of a grade XII student of SMA Pertiwi 1 Padang. Various errors were found in the writing of the structure of the student's scientific work, starting from writing the background of the problem, formulation of the problem, benefits of writing, to writing the results of the research. In addition, errors in writing linguistic elements were also found, such as errors in the use of spelling, effective sentences, to writing bibliographies.The solution offered to this problem is to provide assistance in the form of providing motivation and practice to improve skills and interest in writing scientific papers.The activities in this training use lecture, discussion, and practice methods. Participants follow the training activities very well and can make positive contributions to the results of students' scientific work. This is proven by enthusiasm and increased understanding and the ability to write good scientific papers.. The results of the analysis of students' scientific work data show that as many as 86% of students experienced an increase in understanding and ability in writing scientific works.